The Half-Life-Extended IL21 can Be Combined With Multiple Checkpoint Inhibitors for Tumor Immunotherapy - Wu, Shaoxian; Sun, Runzi; Tan, Bo; Chen, Bendong; Zhou, Wenyan; Gao, David Shihong; Zhong, Joshua; Huang, Hao; Jiang, Jingting; Lu, Binfeng (Frontiers in Cell and Developmental Biology, 2021)
In the era of immune checkpoint blockade cancer therapy, cytokines have become an attractive immune therapeutics to increase response rates. Interleukin 21 (IL21) as a single agent has been evaluated for cancer treatment with good clinical efficacy. However, the clinical application of IL21 is limited by a short half-life and concern about potential immune suppressive effect on dendritic cells. Here, we examined the antitumor function of a half-life extended IL21 alone and in combination with PD-1 blockade using preclinical mouse tumor models. We also determined the immune mechanisms of combination therapy. We found that combination therapy synergistically inhibited the growth of mouse tumors by increasing the effector function of type 1 lymphocytes. Combination therapy also increased the fraction of type 1 dendritic cells (DC1s) and M1 macrophages in the tumor microenvironment (TME). However, combination therapy also induced immune regulatory mechanisms, including the checkpoint molecules Tim-3, Lag-3, and CD39, as well as myeloid derived suppressor cells (MDSC). This study reveals the mechanisms of IL21/PD-1 synergism and shed light on rational design of novel combination cancer immunotherapy.